Evaluation of the combined effect of osmotic and Refractance Window drying on the drying kinetics, physical, and phytochemical properties of beet - Calderón-Chiu, C.; Martínez-Sánchez, C.E.; Rodríguez-Miranda, Jesús; Juárez Barrientos, José Manuel; Carmona-García, R.; Herman-Lara, Erasmo (Drying Technology: An International Journal, 2020)
The effect of osmotic dehydration (OD) with different sucrose concentrations and temperatures was studied in combination with drying by Refractance WindowTM (RW) in beet slices with thicknesses of 1 and 5 mm. The color, texture, total polyphenol content (TPC), total flavonoid content (TFC), and antioxidant capacity (AC) of the beet with OD, RW, and OD-RW combined drying were evaluated. The best results of water loss (WL) and solid gain (SG) with OD were obtained with 65% sucrose solution at 60 °C. OD partially reduced the water content of the slices, decreasing the drying time with RW at 85 °C. However, the retention of qualities such as color, texture, TPC, TFC, and AC in beet was obtained with combined drying by OD-RW at 60 °C under OD conditions of 65% sucrose at 45 °C. These conditions afforded a stable product retaining its physical and chemical properties.
Keywords: Deshidratación osmótica; Ventana de Refractancia